Pemberdayaan Masyarakat: Sebuah Strategi Memperkecil Kesenjangan di Jawa Timur - Abipraja, Soedjono (Jurnal Widya Manajemen & Akuntansi, 2002)
Pemberdayaan comes from the English word "empowerment. The word power in empowerment means daya in Indonesia. Empowerment tends to release the hand cuff of poverty and underdevelopment also to strength the position of society level in authority structure. The effort to increase society empowerment can be seen from three point of view : creating atmosphere that may develop society potention, strengthening society position and power also empowering that contain protection. Society empowerment demands some prerequisite or conditions, are there is empowerment condition, giving the opportunity that make society become empower, protection in order lo develop empowering, increasing ability to become more empowering and government function. The increasing of society capacity and even distribution income marked with the increasing of poor family that can fulfill their basic and social need, is one of the measuring or indicators I he success of empowerment programs.